Extraction, chemical composition, and characterization of potential lignocellulosic biomasses and polymers from corn plant parts - Ibrahim, M. I. J.; Salit, Mohd Sapuan; Zainudin, E. S.; Mohamed Yusoff, Mohd Zuhri (College of Natural Resources, North Carolina State University, 2019)
Corn is a plant that can be used as a potential source of biomass for various biomaterial applications. Thermoplastic corn starch and corn hull, husk, and stalk fibers were extracted from different corn plant parts. The chemical composition, physical properties, thermal stability, crystallinity index, and surface morphology of the extracted samples were characterized on a powder basis. The corn husk and corn starch revealed an excellent combination of properties. Corn husk provided the highest cellulose content as well as the most favorable surface morphology. Corn starch revealed acceptable amylose content and tolerable thermal stability. The cellulose and starch demonstrated an excellent correlation between the function and structure of biomolecules. Hence, both corn starch and husk have potential for use in many applications of the biomaterial.